Analysis of the effects of Reward and Punishment on Employee Performance in the Goods Delivery Service Industry - Mawarida, Apriliani; Hermawati, Lusi; Agustian, Wahid Rahmat; winanti, winanti; Goestjahjanti, Francisca; Sopyan, Dedi; Hasna, Shoftwatun; Tiara, Beby; Ngadiyono, Ngadiyono (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
The purpose of this study was to determine the conditions for giving Reward and Punishment to employee performance. The research variables consist of: Reward (X1), Punishment (X2) and Employee performance (Y). This research was conducted with a quantitative approach. This research is verified with the research method is non-experiment with survey method. Respondents of this study were Office employees. Data collection was carried out by distributing questionnaires to 55 respondents. Data analysis and hypothesis testing using multiple regression. The results of research and hypothesis testing show that: (1) the provision of rewards has a strong and positive relationship with employee performance achievement. (2) punishment has a significant influence on employee performance achievement. (3) partially, the provision of rewards together with punishment has a significant effect on employee performance